2020
DOI: 10.1080/10717544.2020.1837292
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of anlotinib hydrogel enhances antitumor effects and reduces toxicity in mouse model of lung cancer

Abstract: This study was conducted to determine the antitumor effects and ability of an anlotinib (AL) hydrogel (AL–HA–Tyr) to reduce toxicity in a mouse model of Lewis lung cancer (LLC). We constructed a drug carrier system for AL, verified its effectiveness and systemic safety, and provided a preliminary experimental foundation for clinical carrier transformation. AL–HA–Tyr was prepared by encapsulating AL with hyaluronic acid–tyramine (HA–Tyr) conjugates. Colony and tube formation assays showed that AL–HA–Tyr restrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…In each time point, 1 ml of PBS outside the lysis bag was taken out and 1 ml of fresh PBS at corresponding pH value was added. Finally, the amount of Anlotinib hydrochloride in the 1 ml of PBS was determined by High Performance Liquid Chromatography at 220 nm based on the previous report ( Gao et al, 2020 ). Then, the accumulated drug release was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In each time point, 1 ml of PBS outside the lysis bag was taken out and 1 ml of fresh PBS at corresponding pH value was added. Finally, the amount of Anlotinib hydrochloride in the 1 ml of PBS was determined by High Performance Liquid Chromatography at 220 nm based on the previous report ( Gao et al, 2020 ). Then, the accumulated drug release was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…NSCLC is a solid tumor that is highly vascularized. Studies have shown that the growth and metastasis of solid tumors are supported by angiogenesis ( 7 , 8 ). It is known that tubulin inhibitors are the main drugs for the treatment of NSCLC, with the effect of altering microtubule dynamics and inhibiting angiogenesis ( 9 ).…”
mentioning
confidence: 96%
“…The same has been observed with radiotherapy 35 - 37 . With local intratumoral therapy less adverse effects have been observed 38 , 39 . Moreover; the issue method of administration, should be easy for the patient and without complication.…”
Section: Discussionmentioning
confidence: 99%